2011
DOI: 10.1075/sic.8.1.06mon
|View full text |Cite
|
Sign up to set email alerts
|

Las keys versus el key

Abstract: Previous research on language mixing has revealed similarities in written and oral production with respect to syntactic and pragmatic patterns (e.g. Callahan 2004). In this study we find, however, that the two modes of expression diverge in loanword gender assignment. English-origin NPs inserted into written Spanish discourse (e.g. un baggie) were analyzed and compared to English-origin NPs in oral Spanish discourse. Results showed that loanwords are assigned feminine gender at significantly higher rates in wr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Blokzijl et al., 2017). Similarly, many studies have reported a masculine tendency in the assignment of grammatical gender for Spanish-English mixed NPs similar to the sentences in (4a) and (4b) below (Montes-Alcalá and Lapidus Shin, 2011; Valdés Kroff, 2016; cf. Liceras et al., 2008).…”
Section: On the Differential Behavior Of Masculine And Feminine Gendesupporting
confidence: 59%
See 1 more Smart Citation
“…Blokzijl et al., 2017). Similarly, many studies have reported a masculine tendency in the assignment of grammatical gender for Spanish-English mixed NPs similar to the sentences in (4a) and (4b) below (Montes-Alcalá and Lapidus Shin, 2011; Valdés Kroff, 2016; cf. Liceras et al., 2008).…”
Section: On the Differential Behavior Of Masculine And Feminine Gendesupporting
confidence: 59%
“…Because most English words differ from typical Spanish words with respect to their phonological shape (Clegg, 2010; Butt and Benjamin, 2013), it is difficult to determine whether the masculine default strategy is, at least to some degree, driven by phonological factors (Poplack et al., 1982; DuBord, 2004; Montes-Alcalá and Lapidus Shin, 2011). Below, we consider two recent studies that examined how the phonological shape of nouns from different source languages (i.e., Basque and Purepecha) can influence the choices speakers make in terms of the choice of gender assignment.…”
Section: On the Differential Behavior Of Masculine And Feminine Gendementioning
confidence: 99%
“…Poplack, Pousada, & Sankoff, 1982;Zamora, 1975;Zamora Munnt & Btjar, 1987). A preference for masculine gender assignment has been suggested in several previous studies, among L2 learners (Martinez-Gibson, 2011), bilinguals (Chaston, 1996;Clegg, 2010: 16;Garcia, 1998;Montes-Alcalá & Lapidus Shin, 2011;Sánchez, 1995: 134-137), and monolinguals (Banfield, 1994;Pérez-Pereira, 1991;Smith, Nix, Davey, López Ornat, & Messer, 2003).…”
Section: Gendermentioning
confidence: 83%
“…Biological Gender and Animacy I subsequently examined overtly gender-marked dps in terms of biological gender and animacy (Clegg, 2006;DuBord, 2004;Montes-Alcalá and Lapidus Shin, 2011;Otheguy and Lapidus, 2003), two factors that have been shown to be operative in the gender assignment process. Researchers, such as Clegg (2006), postulate that biological sex of the animate referent overrides any other potential factor.…”
Section: 4mentioning
confidence: 99%